Effects of PepSoyGen processing method on nursery pig growth performance - A B Clark; Hyatt L Frobose; Joel M DeRouchey; Michael D Tokach; Steven S Dritz; Robert D Goodband; Jason C Woodworth (Kansas Agricultural Experiment Station Research Reports, 2014)
A total of 292 weanling pigs (PIC 327 × 1050; 13.3 ± 2.4 lb BW and 21 d of age) were used in a 31-d experiment evaluating the effects of alternative PepSoyGen processing methods for nursery pig diets. There were 11 replicate pens per treatment and 6 or 7 pigs per pen. At weaning, pigs were allotted to pens by initial weight to 1 of 4 treatments in a completely randomized design. A 3-phase diet series was used with treatment diets fed during Phase 1 (d 0 to 7) and Phase 2 (d 7 to 21), with a common diet fed from d 21 to 31. Diets were: (1) negative control (corn, soybean meal, and dried whey), (2) positive control (4% DPS 50 + 1% PepSoyGen), (3) PepSoyGen processing method 1 (PSG1; 5%), and (4) PepSoyGen processing method 2 (PSG2; 5%). The alternative PepSoyGen processing methods incorporated increasing levels of a proprietary additive post-fermentation (PSG2>PSG1) aimed at further breakdown of anti-nutritional factors associated with soybean meal. Nutrient analyses generally matched formulated levels for negative and positive control diets, but for both PSG1 and PSG2, CP and amino acid concentrations were lower than formulated, with PSG1 generally 10% lower than PSG2. In Phase 1, pigs fed the positive control diet had improved (P<0.01) ADG and feed efficiency compared with pigs fed the negative control, whereas pigs fed PSG1 and PSG2 diets were intermediate for feed efficiency but tended (P<0.07) to have increased ADG compared with those fed the negative control. For Phase 2, there were no significant differences in growth performance between treatment diets. For the overall experimental period (d 0 to 21), pigs fed the positive control diet and PSG2 diet had improved ADG (P<0.05), whereas pigs fed the positive control, PSG1, and PSG2 diets had improved feed efficiency (P<0.05) compared with pigs fed the negative control diet. Also, pigs fed PSG1 tended (P<0.06) to have lower ADG compared with pigs fed the positive control diet. During the Phase 3 common period, no difference in growth performance was observed. Overall (d 0 to 31), ADG was greater (P<0.01) for pigs fed the positive control diet and tended to be greater (P<0.07) for pigs fed diets containing PSG2 than the negative control diet, with pigs fed PSG1 intermediate. In conclusion, pigs fed the PSG1 or PSG2 diets had similar performance to pigs fed the positive control diet. Numerically, the PSG2 diet elicited greater performance than the PSG1 diet, but it is unclear whether this response is reflective of the reduced CP and amino acid content in the PSG1 diet or if the differences in processing method affected growth response.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Dried porcine solubles; Fermented soybean meal; Growth; Nursery pig; Protein sources